2022
DOI: 10.1007/s10694-022-01346-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mass Timber Compartment Fires on Façade Fire Exposure

Abstract: This study investigates whether timber surfaces that are initially exposed to fire or partially protected timber components can lead to a more critical fire exposure on the façade. Five full-scale fire tests were carried out. Three tests with a square compartment (4.5 × 4.5 m2) and two with a double-width compartment (4.5 × 9 m2). The tests were conducted with a high fire load density (1085 MJ/m2). While the first test was carried out in a non-combustible compartment, the exposed timber surfaces were subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…The majority of small-and medium-scale compartment fire experiments conducted to date have shown that this can result in larger external flames [7], [8] and increased heat flux to both the building of fire origin and opposite [9] than from an otherwise identical compartment constructed from non-combustible materials. One experimental series, with a very high movable fuel load (of 1085 MJ/m 2 ), did not observe a significant increase in flame height when mass timber was introduced, but did report higher temperatures [10]. Significant external flaming was also observed during the large-scale CodeRed experimental series [11]- [13].…”
Section: Exposed Mass Timber and External Flamingmentioning
confidence: 96%
“…The majority of small-and medium-scale compartment fire experiments conducted to date have shown that this can result in larger external flames [7], [8] and increased heat flux to both the building of fire origin and opposite [9] than from an otherwise identical compartment constructed from non-combustible materials. One experimental series, with a very high movable fuel load (of 1085 MJ/m 2 ), did not observe a significant increase in flame height when mass timber was introduced, but did report higher temperatures [10]. Significant external flaming was also observed during the large-scale CodeRed experimental series [11]- [13].…”
Section: Exposed Mass Timber and External Flamingmentioning
confidence: 96%
“…BS EN 13501-2:2016 defines the performance of an encapsulation system to protect a substrate, with the designation of a K2 classification [2]. The standard requires the encapsulation system to limit the temperature increase at the surface of the substrate to below 250 ℃ on average or 270 ℃ in any location while preventing the 1 Arup London, eirik.christensen@arup.com 2 Arup London, benjamin.khoo@arup.com 3 Arup Manchester, panos.kotsovinos@arup.com 4 Arup Melbourne, david.barber@arup.com 5 Arup London, judith.schulz@arup.com pyrolysis of the protected material when exposed to a "standard fire". In addition, there can be no collapse of the covering during the test.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature distribution within real fires is such that the thermal severity of a floor may be expected to be less than that of a ceiling in a timber compartment. Studies found that, in a ventilation controlled fire, gas temperature near the floor are on average 100 -200 °C lower than near the ceiling [3][4][5][6][7], as shown in Figure 1. As such applying the same fire protection for encapsulation on both the ceiling and floor may result in excessive conservative encapsulation, inflating the mass, embodied carbon, and cost of a building.…”
Section: Introductionmentioning
confidence: 99%